The Looming Dangers of Explosion in Community Transmissions of COVID-19 in Nigeria - Agaptus Nwozor; Charles Okolie; Onjefu Okidu; Segun Oshewolo (Ubiquity Press, 2020)
Currently, Nigeria is still at the ascending phase of the COVID-19 curve with no sign of deceleration. Thus, the recent decision by governors of states in northern Nigeria to deport Almajirai (itinerant Islamic school pupils) from their states as part of efforts to contain COVID-19 transmission is likely to have a serious backlash. With hundreds of Almajirai testing positive to COVID-19, and millions of others untested, they constitute ubiquitous nodes of transmission. Their deportation has created multiple emigration channels that constitute prospective feeders to covert community transmission. This viewpoint examines this trend within the context of Nigeria's current [in]capacity to manage the spread of COVID-19 and concludes that greater risks seem to lie ahead unless the government takes stringent containment measures.